2022
DOI: 10.1002/ajmg.a.63100
|View full text |Cite
|
Sign up to set email alerts
|

TRAPPC9‐related neurodevelopmental disorder: Report of a homozygous deletion in TRAPPC9 due to paternal uniparental isodisomy

Abstract: TRAPPC9 loss‐of‐function biallelic variants are associated with an autosomal recessive intellectual disability syndrome (Online Mendelian Inheritance of Man no. 613192), also characterized by microcephaly, hypertelorism, obesity, growth delay, and behavioral differences. Here, we describe an 8‐year‐old Hispanic female with neurodevelopmental disorder, partial epilepsy, microcephaly, bilateral cleft lip and alveolus, growth delay, and dysmorphic features. She had abnormal myelination, mega cisterna magna, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…We show that the brain abnormalities identified in Trappc9 KO mice also result in behavioural deficits related to anxiety, cognition, learning and memory, which might reflect some the intellectual disability symptoms of human patients (Amin et al, 2022;Aslanger et al, 2022;Ben Ayed et al, 2021;Bolat et al, 2022;Hnoonual et al, 2019;Koifman et al, 2010;Kramer et al, 2020;Mir et al, 2009;Mochida et al, 2009;Penon-Portmann et al, 2023;Philippe et al, 2009;Radenkovic et al, 2022). Our open field test data demonstrate an overall reduced locomotor activity of Trappc9 KO mice, which is consistent with recent findings from other Trappc9 mouse lines (Hu et al, 2023;Ke et al, 2020;Liang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We show that the brain abnormalities identified in Trappc9 KO mice also result in behavioural deficits related to anxiety, cognition, learning and memory, which might reflect some the intellectual disability symptoms of human patients (Amin et al, 2022;Aslanger et al, 2022;Ben Ayed et al, 2021;Bolat et al, 2022;Hnoonual et al, 2019;Koifman et al, 2010;Kramer et al, 2020;Mir et al, 2009;Mochida et al, 2009;Penon-Portmann et al, 2023;Philippe et al, 2009;Radenkovic et al, 2022). Our open field test data demonstrate an overall reduced locomotor activity of Trappc9 KO mice, which is consistent with recent findings from other Trappc9 mouse lines (Hu et al, 2023;Ke et al, 2020;Liang et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we demonstrate by using MRI that the microcephaly of Trappc9 KO mice has a postnatal onset and is clearly established at weaning age. These findings are in line with TRAPPC9 patient data, which show microcephaly within the first year of life (Amin et al, 2022; Aslanger et al, 2022; Ben Ayed et al, 2021; Bolat et al, 2022; Hnoonual et al, 2019; Koifman et al, 2010; Penon-Portmann et al, 2023; Radenkovic et al, 2022) as well as data from other recently published Trappc9 KO mouse studies, which reported differences at postnatal days 7, 15 and 20, but not at birth (Hu et al, 2023; Ke et al, 2020). Monogenic disorders causing postnatal-onset microcephaly are less common than those causing primary microcephaly, which are mostly due to cell proliferation defects during embryogenesis.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Mutations in TRAPPC9 are associated with non-syndromic autosomal recessive intellectual disability (NS-ARID), assigned as "Intellectual Disability-Obesity-Brain Malformations-Facial Dysmorphism Syndrome" and "Intellectual developmental disorder, autosomal recessive 13" (OMIM #613192), and abbreviated as NIBP syndrome [24,28]. Loss-of-function TRAPPC9 mutations manifest microcephaly, intellectual disability, and obesity in patients [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Magnetic resonance imaging in affected individuals with NIBP syndrome has revealed reduced cerebral white matter volume with sulcal enlargement, thinning of the corpus callosum, and mild cerebellar volume loss [29][30][31].…”
Section: Introductionmentioning
confidence: 99%